Computer Assisted Instruction (CAI) Integrated Case Method-Flipped Classroom: Innovative Instructional Model to Improve Problem-Solving Skill and Learning Outcome of TVET Students - Wulansari, Rizky Ema; Marta, Rizkayeni; Sakti, Rizki Hardian; Dewi, Siska Miga; Safitri, Dian; Kassymova, Gulzhaina Kuralbayevna; Folkourng, Fan; Kumar, Vimal (Journal of Technical Education and Training, 2023)
The post-pandemic has affected all educational institutions, including TVET. The situation has shifted fully online learning into a blended one, conducted online through e-learning and onsite through face-to-face learning. In this learning, students must do self-directed learning before coming to the class, known as the flipped classroom method. On the other hand, to trigger their effort to do so, applying the case method is valuable to improve their problem-solving skill. Therefore, the flipped classroom and case method integration needs to be implemented. In the flipped classroom method, students must use CAI media to optimise the learning outcome. This study aims to see the effectiveness of integrating CAI into case method-flipped classrooms in improving the problem-solving skills and learning outcomes of TVET students. This study used a quasi-experiment with a pre-test and post-test control group design. The research instruments were a questionnaire and an achievement test with 62 participants. Based on the results, it was found that there was a significant difference in students’ problem-solving skills and learning outcomes between control and experimental groups. Research findings showed substantial improvements in students’ material understanding and problem-solving skills. Students reported high engagement and satisfaction with the proposed interactive learning model. Thus, it can be concluded that the CAI-integrated Case Method-Flipped Classroom effectively improves TVET students’ problem-solving skills and learning outcomes. The novelty of this research is that it offers an innovation from various learning models in TVET that TVET educators can implement. The model provides time efficiency availability of such a lead-in that bridges the initial material to the primary material. Hence, the investigation results in this study provide a new knowledge reference for the TVET education curriculum.